2021
DOI: 10.1063/5.0050488
|View full text |Cite
|
Sign up to set email alerts
|

Controllable probe absorption spectrum via vortex beams excitation in a cascaded atomic system

Abstract: Dynamic control of probe absorption spectrum via vortex beams in multilevel systems has attracted much attention because it provides an avenue to observe unique transport properties. In this paper, we employ experimentally accessible parameters to flexibly control the probe absorption spectrum that shows vortex-induced transparency (VIT) and absorption (VIA) phenomena. Specifically, this system can be served as an optical switch while the vortex beams can act as the control knob, which has the ability to switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In 2015, Radwell et al experimentally observed spatially dependent EIT via using Laguerre-Gaussian (LG) vortex beam to drive cold rubidium atoms [29]. Since then, the interaction between LG beam and atomic system has led to many interesting quantum optical phenomena, such as spatial absorption [30,31], spatially structured Kerr nonlinearity [32], ultraprecise Rydberg atomic localization [33], Ferris wheel patterning [34], vortex four-wave mixing (FWM) [35][36][37][38] and spatially dependent hyper Raman scattering [39]. Such proposals have the obvious advantage of all-optical controllable capability.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Radwell et al experimentally observed spatially dependent EIT via using Laguerre-Gaussian (LG) vortex beam to drive cold rubidium atoms [29]. Since then, the interaction between LG beam and atomic system has led to many interesting quantum optical phenomena, such as spatial absorption [30,31], spatially structured Kerr nonlinearity [32], ultraprecise Rydberg atomic localization [33], Ferris wheel patterning [34], vortex four-wave mixing (FWM) [35][36][37][38] and spatially dependent hyper Raman scattering [39]. Such proposals have the obvious advantage of all-optical controllable capability.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, numerous schemes for the spatially dependent light-matter interaction induced by LG beams have been proposed in cold atomic ensembles [41], rareearth-doped crystal [42], two-dimensional array of metal-coated dielectric nanosphere [43], semiconductor quantum dots [44], and molecular magnets [45]. Meanwhile, many intriguing quantum optical phenomena have been discovered such as vortex-induced spatial absorption [46,47], spatially structured Kerr nonlinearity [39], ultraprecise Rydberg atomic localization [48], vortex four-wave mixing (FWM) [44,45,49,50,51,52], and spatially dependent hyper Raman scattering [53]. Recently, semiconductor quantum wells (SQWs) have been exploited to explore the transfer and control of mid-infrared LG beams due to their inherent advantages such as high nonlinear optical coefficient and large electric dipole moments of intersubband transitions [54,55,56].…”
Section: Introductionmentioning
confidence: 99%